JOURNALISM TEACHING PRACTICE DURING THE COVID-19 PANDEMIC: QUALITATIVE ANALYSIS OF TEACHERS’ ATTITUDES - Osepashvili, Dali (International Journal of Innovative Technologies in Social Science, 2022)
The transition to full online teaching format has posed a number of challenges of journalism higher education. The goal of this research is to show Georgian journalism teachers’ attitudes towards online learning during the covid-19 pandemic. To reach this goal and explore this issue a social constructivism framework is used. The main research questions: How effective is this process? What are the strengths and weakness of full online learning? What opportunities of the development are arisen? This study is based on the qualitative approach and a semi-structured interviews method is used for this research. The interviews (n=17) were conducted among journalism professors, different Georgian media schools. This study was carried out from 20 June till 20 October 2021. According to the results of this study, there are a lot of challenges facing during the full remote classes but nevertheless there are a number of development opportunities. At the end of the research the author suggests certain recommendations for media schools.